Case for diagnosis Caso para diagnóstico - Fernanda Homem de Mello de Souza Klein; Renata Homem de Mello de Souza Alves; André Homem de Mello de Souza (Sociedade Brasileira de Dermatologia, 2013)
Pigmentary demarcation lines are physiologically abrupt transition lines from areas of deeper pigmentation to less pigmented areas. They are most often seen in African and Japanese individuals and rarely observed in Caucasians. There are eight types of pigmentary demarcation lines. The one described here, type B, is restricted to women and is associated with pregnancy in non-black patients. This type of pigmentary demarcation line occurs in the posterior aspect of the legs, extending from the perineum to the ankle. Its distribution follows the Voigt's lines, which define the distribution of peripheral nerves. Its pathogenesis remains unknown. Expectant treatment is used, and good results have been reported with the use of Q-switched Alexandrite laser. Linhas de demarcação pigmentar são linhas fisiológicas que correspondem a transições abruptas entre áreas mais escuras e mais claras. São mais comuns em africanos e japoneses, mas raras em brancos. Há 8 tipos, sendo a aqui descrita, tipo B, restrita a mulheres e relacionada a gestação em não negras. Este tipo de linha de demarcação pigmentar ocorre na face posterior dos membros inferiores estendendo-se do períneo ao tornozelo. Estas se localizam nas linhas de Voigt que são o trajeto dos nervos periféricos. Sua fisiopatogenia é incerta. O tratamento é expectante com relato de bom resultado com Q-switchedAlexandrite laser.